Hadapi Pandemi Covid-19 Dalam Pemberdayaan Pemerataan Di Perdesaan Dalam Manipol Usdek Sebagai Perspektif Pendidikan Politik Nawacita Jokowi Di Era Milenial - I Ketut Kasna (Universitas Mahendradatta Denpasar, 2021)
Inequality and poverty, especially in rural areas, are one of the challenges of the Indonesian nation. Compared to cities, the proportion of poor people due to the dilemma facing the Covid-19 pandemic is much higher in rural areas. Especially in remote villages, rural areas or underdeveloped areas, the conditions are much more apprehensive. Therefore, rural development is a priority. Large amounts of Village Funds are distributed and continue to increase every year for empowering the local economy, creating access to local transportation and fulfilling basic infrastructure as well as financing due to the dilemma facing the Covid-19 pandemic. To tackle poverty due to the Covid-19 pandemic in rural areas and overcome inequality between villages and villages and cities, the government has established a strategy of